MED12 mutation induces RTK inhibitor resistance in NSCLC via MEK/ERK pathway activation by inflammatory cytokines - Hyun-Min Ryu; Deokhoon Kim; Jun Young Choi; Shinkyo Yoon; Ho-Su Lee; Ji Eun Park; Eunjin Lee; Yunkyung Sung; Chang Hoon Lee; Eun-Young Lee; Wanlim Kim; Seyoung Seo; et al. (Cellular and Molecular Life Sciences)
Abstract Non-small cell lung cancer (NSCLC) is frequently associated with mutations in receptor tyrosine kinases (RTKs), such as EGFR and ALK. While RTK inhibitors (RTKIs) have proven effective in treating patients with specific RTK mutations, the emergence of resistance to these therapies remains a significant clinical obstacle. As such, there is still an unmet need for the identification of new biomarkers that can predict resistance to RTK inhibitors in clinical use. In the present study, we demonstrate that MED12 mutations are a key driver of RTKi resistance in NSCLC cells. This resistance is mediated through the release of inflammatory cytokines triggered by MED12 degradation. Notably, we observed that of the two major downstream signaling pathways activated by inflammatory cytokines, only the MEK/ERK pathway was upregulated, while the PI3K/AKT pathway was unaffected in MED12 knock-out (KO) cells. The degradation of MED12 results in the dissociation of the MED12 complex, which subsequently leads to YAP phosphorylation. This phosphorylated YAP increases PTEN expression by inhibiting miR-29, thereby suppressing the PI3K/AKT signaling pathway. Importantly, treatment with trametinib, a MEK inhibitor, effectively suppressed tumor growth in MED12KO NSCLC cells and in xenograft models derived from these cells. These findings suggest that targeting the MEK/ERK signaling pathway, such as with trametinib, may provide a viable strategy to overcome RTKi resistance in MED12-mutant NSCLC. Furthermore, MED12 is identified as a crucial biomarker and potential therapeutic target for overcoming RTKi resistance.